Inhysning av struts - Bergdahl, Ida (2006)
The Swedish ostrich production started about thirteen years ago and still there are no Swedish recommendations regarding ostriches' space requirements. The European Council give recommendations and the Swedish Board of Agriculture (SJV) has a proposal, but so far the producers follow Danish regulations regarding space requirements. The Swedish Animal Welfare Agency are about to set standards for the ostriches' space requirements, and therefore the Swedish ostrich producers, together with The Federation of Swedish Farmers (LRF) ask for a scientific background to these decisions.